PENGUATAN NILAI MODERASI BERAGAMA MELALUI SUPERVISI KOLABORATIF PADA GURU PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 2 MOJOLABAN - Ainunajip, Muhammd Nur; Jati, Arfian Darma; Abbas, Ngatmin (Jurnal Manajemen Pendidikan, 2025)
Religious moderation is a strategic program initiated by the Ministry of Religious Affairs of Indonesia, emphasizing the importance of tolerance, fairness, and respect for diversity in religious life. In the educational context, PAI teachers play a central role in transmitting these values through the learning process. This study uses a descriptive qualitative method with data collection techniques including interviews, classroom observations, and documentation studies. The findings reveal that collaborative supervision at State Junior High School 2 Mojolaban is carried out through joint planning, classroom supervision, and post-teaching reflection. PAI teachers are encouraged to incorporate values of moderation, such as interfaith tolerance, rejection of extremism, and appreciation for cultural and religious diversity. Challenges encountered include limited supervision time and insufficient understanding of religious moderation concepts among some teachers. Nevertheless, collaborative supervision has proven effective in enhancing teachers’ pedagogical awareness and their ability to contextually integrate religious moderation values into the teaching and learning process. This study recommends increased training and ongoing support for PAI teachers to foster a culture of moderate and inclusive education.